18.2k views
3 votes
-x^2+15x-44
factor the equation

User Berkobienb
by
5.1k points

1 Answer

0 votes

Answer:

- (x - 4)(x - 11)

Explanation:

Given

- x² + 15x - 44 ← factor out - 1 from each term

= - 1 (x² - 15x + 44) ← factor the quadratic

Consider the factors of the constant term (+ 44) which sum to give the coefficient of the x- term ( - 15)

The factors are - 4 and - 11 , since

- 4 × - 11 = + 44 and - 4 - 11 = - 15 , thus

x² - 15x + 44 = (x - 4)(x - 11) and

- x² + 15x - 44 = - (x - 4)(x - 11)

User Carrosive
by
5.1k points